Endothelin-based markers for endothelial dysfunction in chemotherapy-induced cardiotoxicity - Gabrielle Boutin; Jale Yuzugulen; Md Zahidul Islam Pranjol (Journal of Molecular and Cellular Cardiology Plus, 2023)
Current cardiac biomarkers, troponins and brain natriuretic peptide, are primarily used to assist in the diagnosis or exclusion of myocardial damage and congestive heart failure, respectively. The use of these biomarkers in chemotherapy-induced cardiotoxicity has been evaluated by various studies. However, neither biomarker provides early predictive value, leaving many cancer survivors with irreversible cardiac injury. Assessing endothelial dysfunction could be an effective measure of chemotherapy-induced cardiotoxicity at the vascular level. Risk profiling and detection of vascular toxicities may offer predictive biomarkers to prevent chronic manifestation of irreversible cardiotoxicities. Emerging interest has developed in finding biomarkers that could ideally provide earlier prognostic value. Thus, the aim of this review is to give an overview of current blood-based cardiac biomarkers and discuss the potential of endothelin-1 (ET-1) and more stable peptide fragments of ET-1 synthesis as biomarkers of endothelial dysfunction. For instance, endothelin-like domain peptide (ELDP) and C-terminal pro-endothelin-1 (CT-proET-1) demonstrated high-sensitivity and longer clearance rate than ET-1. Thus, investigating their biomarker role in chemotherapy-induced cardiotoxicity is important and could provide additional insights for identifying patients at risk. Also, additional research is required to fully understand ELDP-mediated vasoconstriction. This review will discuss the future development of ET-1, ELDP and CT-proET-1 as prospective predictive biomarkers.